The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1980-549720200071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de sonolência diurna excessiva e fatores associados em adolescentes da coorte RPS, em São Luís (MA)

Abstract: RESUMO: Objetivos: Estimar a prevalência de sonolência diurna excessiva (SDE) e os fatores associados a ela em adolescentes da coorte de nascimentos de São Luís (MA). Método: Estudo transversal realizado com 2.514 adolescentes com idade de 18 e 19 anos. Utilizou-se abordagem hierarquizada e calculou-se a razão de prevalências utilizando regressão de Poisson com ajuste robusto da variância. Foram estudadas características sociodemográficas (sexo, cor, classe econômica, ocupação), hábitos de vida (lazer, fum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
3
1
3
Order By: Relevance
“…Regarding EDS, the observed prevalence was 51.3%, which can be considered high in comparison to 36.8% and 32.2% observed in other studies, which were carried out with a population of the same age group and using the same assessment instrument 33,34 . These studies also found a higher prevalence of EDS in women compared to men.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Regarding EDS, the observed prevalence was 51.3%, which can be considered high in comparison to 36.8% and 32.2% observed in other studies, which were carried out with a population of the same age group and using the same assessment instrument 33,34 . These studies also found a higher prevalence of EDS in women compared to men.…”
Section: Discussioncontrasting
confidence: 52%
“…These behaviors may contribute to the maintenance of a regular sleep schedule, which is related to the observed lower rate of daytime sleepiness 34 . Considering that the literature points out that students tend to wake up earlier during the week, due to the class schedule and spontaneously sleep and wake up later on the weekend 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Com relação à SDE, a prevalência observada foi de 51,3%, índice considerado maior em relação aos resultados obtidos em outros estudos (36,8% e 32,2%) que foram realizados com público de mesma faixa etária e utilizando o mesmo instrumento de avaliação 33,34 . Esses estudos também observaram maior prevalência de SDE nas mulheres em relação aos homens.…”
Section: Demanda Acadêmicaunclassified
“…Esses comportamentos podem estar contribuindo para a manutenção de uma regularidade nos horários de sono, a qual está relacionada à menor sonolência diurna observada 34 . De acordo com a literatura, os estudantes tendem a acordar mais cedo na semana, devido ao horário das aulas, e dormir e acordar, espontaneamente, mais tarde no fim de semana 33,34 fisiológica ao indivíduo, de modo a gerar um viés de percepção do estudante ao preencherem a escala de avaliação da sonolência diurna. Ademais, há diferenças individuais com relação à necessidade biológica da duração de sono 39 .…”
Section: Demanda Acadêmicaunclassified
“…Some factors may contribute to an increase in the deleterious effects of sleep duration [ 5 ], such as demographic, socioeconomic [ 3 , 9 ], and behavioral [ 3 ] characteristics and food choices [ 10 ]. There is evidence that the high consumption of ultra-processed foods [ 11 ] may lead to reduced sleep durations in adolescents.…”
Section: Introductionmentioning
confidence: 99%